A alfabetização de crianças com diagnóstico de deficiência intelectual: um estudo de caso em uma escola pública municipal - Perpetuo, Regina Célia Fernandes da Costa (2020)
In this study is proposed as subject of study two children’s literacy process diagnosed as intellectual disability. Starting from this study subject some concern rose which drove and guided the development of this study. Is it possible literate intellectual disable children? If it is possible, how does it happen? How the legislation proposed measures are converted into effective in loco at places? Starting by the questions proposed, we have delimited tounderstand how this process is developed as this study general aim. It was listed as specific objectives (1) to get to know the social and historical aspects from intellectual disability people in order to understand their nowadays conceptions; (2) to understand the environment where the two subject children are in; (3) to watch their learning process and (4) propose interventions based on the study of theoretical references and on previous analysis. This research was developed from the objectives already presented and following a qualitative approach based on documents analysis and in loco watching. Written documents and semi-structured interviews with teachers, managers and those people who are responsible for the two children were the collecting data source. A public school from Mogi das Cruzes, Sao Paulo state, Brazil, was the research environment and the subject children were enrolled in the literacy cycle. The theoretical perspective used in this study is based on Vygotsky (1988, 1991, 2000, 2008, 2012); Ferreiro/Teberosky (1985); Soares (2011,2018), also including other authors who have contributed with their considerations about special education, literacy and multiliteracy. It was observed that it is possible to literate intellectual disable children, but, for so, it is necessary to watch over the child potentialities. It was also observed that all the changes proposed by Brazilian Legislation are used, but it is necessary to close look on how those propositions are done at a place. This research contributed with some interventions purposes and identifies positive elements and chunks which influenciates children with diagnosis of intellectual disability development; among them the family lack of motivation, the distance between the accessible curricula and the one which is actually used by students in the classroom and the lack of space and available time to plan the curricular adjustments for the teachers and their auxiliaries, and as the positive aspects: the inclusive profile at school, the host, the app used during the IT classes, the teachers’ involvement and commitment which reveals and brings up the matter of right guarantee of learning for all children and the teaching quality effectuation.